Financing Type And Sustainability Reporting: Financial Performance As Mediating Variable - Falikhatun, Falikhatun; Wahyuni, Salamah; Niswah, Milananda Ainun; Nilasakti, Afifah Oki (Jurnal Dinamika Akuntansi, 2020)
The research aims to examine the effect of financing types on sustainability reporting with financial performance as a mediating variable. The independent variables in this research are Murabahah Musyarakah, and Mudharabah, while the mediating variable in this research is financial performance measured using Capital Adequacy Ratio (CAR) as a proxy. The Population of this research is Islamic Banking listed in statistical of Otoritas Jasa Keuangan Indonesia and published sustainability reporting and annual reports for the 2014-2017 period. The result of this study concluded that Financing Type proxied with Murabahah financing affects financial performance (CAR), and financial performance (CAR) also affects the Sustainability Reporting. The other proxies of financing type (Musyarakah and Mudharabah) do not affect financial performance. This study also concluded that financial performance variable mediates the effect of Financing type (Murabahah) on Sustainability Reporting.Ã‚Â